2020
DOI: 10.3390/microorganisms8010090
|View full text |Cite
|
Sign up to set email alerts
|

A High Resolution DNA Melting Curve Analysis for the Rapid and Efficient Molecular Diagnostics of Extended Spectrum β-Lactamase Determinants from Foodborne Escherichia coli

Abstract: The accurate identification of Extended-Spectrum β-Lactamase (ESBL) genes in Gram-negative bacteria is necessary for surveillance and epidemiological studies of transmission through foods. We report a novel rapid, cheap, and accurate closed tube molecular diagnostic tool based on two multiplex HRM protocols for analysis of the predominant ESBL families encountered in foods. The first multiplex PCR assay targeted blaCTX-M including phylogenetic groups 1 (CTX-M-1-15, including CTX-M-1, CTX-M-3 and CTX-M-15), 2 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…In the last few years, HRM PCR has become more widely applied for epidemiological purposes related to infectious diseases in addition to genotyping yeasts, viruses, or bacteria [23][24][25][26]. Indeed, this technique allows distinction of the different viral or bacterial strains [23][24][25], detection of mutated and wild-type strains [13], mutations located on resistance genes, such as resistance to rifampicin in Mycobacterium tuberculosis [27], or differentiation between Brucella species [28].…”
Section: Discussionmentioning
confidence: 99%
“…In the last few years, HRM PCR has become more widely applied for epidemiological purposes related to infectious diseases in addition to genotyping yeasts, viruses, or bacteria [23][24][25][26]. Indeed, this technique allows distinction of the different viral or bacterial strains [23][24][25], detection of mutated and wild-type strains [13], mutations located on resistance genes, such as resistance to rifampicin in Mycobacterium tuberculosis [27], or differentiation between Brucella species [28].…”
Section: Discussionmentioning
confidence: 99%
“…For the identification of MBL-producing strains, the susceptibility and specificity of the HRMA method were 99.2% and 99.7%, respectively, and were 100% reported for the detection of carbapenemase-producing. Studies in UK, 19 Denmark, 34 and USA 35 have shown that the sensitivity and specificity of HRMA to detect class A and class B β-lactamase are more than all phenotypic methods. However, in these studies, some phenotypic methods were used to detect strains producing ESBL and bla KPC with false positives and false negatives.…”
Section: Figurementioning
confidence: 99%
“…Typically, CTX-M-1 and CTX-M-15 phenotyping and genotyping is performed by antibiotic susceptibility testing followed by CTX-M group specific PCR and DNA sequencing ( 29 32 ), a considerably lengthier and more expensive process than the LEC-LAMP assay approach. Various studies have reported the use of PCR followed by melt analysis for CTX-M-1 and CTX-M-15 differentiation ( 33 35 ), however, these methods require postamplification analysis producing ambiguous results that require discrimination of near identical melt curves often only differing by less than 0.5°C. Further highlighting the utility of this LEC-LAMP assay, Leflon-Guibout and colleagues previously reported a CTX-M-15 specific PCR assay that cannot effectively differentiate CTX-M-15 from CTX-M-1 based on available related nucleotide sequence information ( 36 ).…”
Section: Discussionmentioning
confidence: 99%